25th ANNIVERSARY OF CLONING BY SOMATIC-CELL NUCLEAR TRANSFER Twenty-five years after Dolly: how far have we come?. Issue 1 (16th June 2021) - Klinger, Bernhard; Schnieke, Angelika
Abstract : For more than a century, the scientific consensus stated that a nucleus from a terminally differentiated cell would not be able to control the development of offspring. This theory was refuted by the birth of Dolly, the first animal generated by nuclear transfer using an adult somatic cell as a nuclear donor. Following this paradigm shift, a wide variety of animals has been cloned using somatic cell nuclear transfer. Coupled with modern genome engineering technology, somatic cell nuclear transfer has become the method of choice for the generation of genetically modified farm animals. This has opened new opportunities to study the function of genes and has led to the establishment of animal models for a variety of human conditions and diseases or to improve the health of livestock animals.